The complete chloroplast genome of Ilex 'Emily Bruner', Ilex cornuta 'Burfordii' × Ilex latifolia (Aquifoliaceae). Issue 3 (2nd July 2020) - Zhang, Fan; Li, Yunlong; Sun, Linhe; Zhou, Yanwei; Chen, Hong; Lu, Xiaoqing; Li, Naiwei; Wang, Chuanyong
Abstract: Ilex 'Emily Bruner' is an important economic plant with ornamental and ecological functions in southeastern China. In this study, we characterized the complete chloroplast (cp) genome sequence of 'Emily Bruner' to investigate its phylogenetic relationship. The entire cp genome of 'Emily Bruner' was 157, 216 bp in length with 37.68% overall GC content, including a large single-copy (LSC) region of 86, 721 bp and a small single-copy (SSC) region of 18, 427 bp, which were separated by a pair of inverted repeats (IRs) of 52, 068 bp. The cp genome contained 135 genes, including 90 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Phylogenetic analysis based on whole cp genome sequences showed that 'Emily Bruner' is closest to I. cornuta species.